Myosin VI in the nucleolus of neurosecretory PC12 cells: its involvement in the maintenance of nucleolar structure and ribosome organization - Nowak, Jolanta; Lenartowski, Robert; Kalita, Katarzyna; Lehka, Lilya; Karatsai, Olena; Lenartowska, Marta; Rędowicz, Maria Jolanta (Frontiers in Physiology, 2024)
We have shown previously that unconventional myosin VI (MVI), a unique actin-based motor protein, shuttles between the cytoplasm and nucleus in neurosecretory PC12 cells in the stimulation-dependent manner, and interacts with numerous proteins involved in nuclear processes. Among the identified potential MVI partners was nucleolin, a major nucleolar protein implicated in rRNA processing and ribosome assembly. Now, we show that several other nucleolar proteins such as fibrillarin, UBF (Upstream Binding Factor) and B23 (also termed as nucleophosmin) interact with MVI. A bioinformatic tool predicted the presence of the nucleolar localization signal (NoLS) within the MVI globular tail domain, and immunostaining confirmed the MVI presence within the nucleolus. Depletion of MVI, previously shown to impair PC12 cell proliferation and motility, caused disorganization of the nucleolus and rough endoplasmic reticulum (rER). However, lack of MVI seems not to affect nucleolar transcription. In light of these data, we propose that MVI is important for the nucleolar and ribosome maintenance but not for the RNA polymerase 1-related transcription.